Current Status of Decommissioning and Waste Management at the Ningyo-Toge Environmental Engineering Center. (4th May 2023) - Ohashi, Yusuke; Shimaike, Masamitsu; Matsumoto, Takashi; Takahashi, Nobuo; Yokoyama, Kaoru; Morimoto, Yasuyuki
Abstract: At the Ningyo-Toge Environmental Engineering Center, technical developments related to uranium refining conversion and enrichment have been completed and decommissioning of these facilities has begun. The error between the quantity of dismantled materials estimated from the facility design drawings and the actual quantity of the dismantled materials was about 1.7% when averaged over the entire facilities already dismantled. Most of the dismantled materials, which have no contamination history and were properly managed, were confirmed to have surface radioactivity concentrations below the detection limit and could be carried out to recyclers as nonradioactive (NR) waste. The dismantled materials that could not be certified as NR needed to be cleared and reused. By evaluating two types of gamma rays of 234m Pa from the mockup dismantled objects, it was found that uranium corresponding to a clearance level (1.2 × 10 2 Bq/kg) could be quantified.